Engineering Escherichia coli as a platform for the in vivo synthesis of prenylated aromatics. Issue 5 (28th January 2019) - Qian, Shuai; Clomburg, James M.; Gonzalez, Ramon
Abstract: Prenylated aromatics (PAs) are an important class of natural products with valuable pharmaceutical applications. To address current limitations of their sourcing from plants, here, we present a microbial platform for the in vivo synthesis of PAs based on the aromatic prenyltransferase NphB from Streptomyces sp. strain CL190. As proof of concept, we targeted the prenylation of phenolic/phenolcarboxylic acids, including orsellinic (OSA), divarinolic (DVA), and olivetolic (OLA) acids, whose prenylated products have important biopharmaceutical applications. Although the ability of wild‐type NphB to catalyze the prenylation reaction with each acid was validated by in vitro characterization, improvement of product titers in vivo required protein modeling and rational design to engineer NphB variants with increased activity and product selectivity. When a designed NphB variant with eightfold improved catalytic efficiency toward OSA was expressed in an Escherichia coli host engineered to generate geranyl pyrophosphate at high flux through the mevalonate pathway, we observed up to 300 mg/L prenylated products by exogenously supplying OSA. The improved properties of engineered NphB were also utilized to demonstrate the diversification of this in vivo platform by using both different aromatic acceptors and different prenyl donors to generate various PA compounds, including medicinally important compounds such as cannabigerovarinic, cannabigerolic, and grifolic acids. Abstract : A microbial platform for the synthesis of prenylated aromatic compounds was developed based on functional expression of the soluble aromatic prenyltransferase NphB. Key to this approach was engineering NphB through protein modeling and rational design, resulting in significant improvement to its catalytic efficiency. Expression of an engineered NphB variant coupled with exogenous addition of aromatic substrates and mevalonate pathway engineering for pyrophosphate supply enabled production of various prenylated aromatics, including medicinally important compounds such as cannabigerovarinic, cannabigerolic, and grifolic acids.